Çocuklarda serebral tromboz olgularının değerlendirilmesi - (:unkn) unknown (My University, 2016)
Amaç: Çalışmamızda kliniğimizde serebral sinovenöz tromboz tanısıyla izlenen olguların yaş, cinsiyet, klinik bulgular, etiyoloji, risk etmenleri, görüntüleme bulguları, tedavi ve hastalığın seyri yönünden değerlendirilmesi amaçlandı.Gereç ve Yöntemler: Çocuk Nöroloji Kliniğimizde 1 Aralık 2010 - 31 Aralık 2014 tarihleri arasında serebral tromboz tanısıyla izlenen, 11 hastanın tıbbi kayıtları geriye dönük olarak değerlendirildi. Bulgular: On bir olgunun yedisi erkekti (%63,6). Ortanca yaş 14 idi . Olguların altısı (%54,5) baş ağrısı yakınması ile başvurdu. Diğer başvuru nedenleri; çift görme (n=3), konuşamama, güç kaybı (n=1), nöbet (n=1) idi. Sekiz hastaya psödotumor serebri (%72,7) tanısı konuldu. Etiyolojide üç olguda mastoidit, bir olguda mastoidit ve menenjit birlikte, üç olguda Behçet hastalığı, bir olguda kafa travması saptandı. Üç hastada yalnız protrombotik genetik risk etmenleri mevcuttu; bir hastada protein C ve birlikte protein S eksikliği bir hastada antitrombin 3 eksikliği ve bir hastada hiperhomosisteinemi ve B12 vitamin eksikliği, ek olarak; mastoidit ve menenjiti olan bir hastada homozigot MTFHR A1298C mutasyonu, mastoiditi olan bir diğer hastada protein S eksikliği ve lupus antikoagulanı saptandı. Tüm hastalar antikoagulan tedavi aldı ve bir olgu dışında tüm olgular nörolojik sekelsiz iyileşti. Çıkarımlar: Baş ağrısı ve fokal nörolojik bulgularla ile başvuran hastalarda serebral sinovenöz tromboz akılda tutulmalı, tanı için gerekli görüntüleme tetkikleri istenmelidir. Kulak burun boğaz muayenesi detaylı yapılmalı, mastoidit araştırılmalıdır. Çocuklarda kalıtsal trombofilik etmenlerin rolü olabileceğinden genetik risk etmenlerinin araştırılması önerilir. Etiyolojide ülkemizde görece sık görülen Behçet hastalığı unutulmamalıdır.

Aim: We aimed to evaluate the patients who were followed up in our clinic with a diagnosis of cerebral sinovenous thrombosis in terms of age, sex, clinical findings, etiology, thrombophilic factors, imaging findings, treatment and prognosis.Material and Methods: The files of 11 patients who were followed up in our pediatric neurology clinic with a diagnosis of cerebral thrombosis between 1 December 2010 and 31 December 2014 were retrospectively analyzed.Results: Seven of 11 patients were male (63.6%). The median age was 14 years (2-17 years). Six (54%) of the patients presented with a complaint of headache. Other complaints at presentation included diplopia (n:3), weakness and difficulty in speaking (n:1) and seizure (n:1). A diagnosis of pseudotumor cerebri was made in eight of the patients (72.7%). In the etiology, mastoiditis was found in three patients, mastoiditis and meningitis were found in combination in one patient, Behçet's disease was found in three patients and head trauma was found in one patient. In 3 patients, only prothrombotic genetic risk factors were present; one patient had deficiency of protein C and S, one patient had deficiency of antithrombin III and one patient had hyperhomosisteinemia in association with vitamin B12 deficiency. 1A homozygous MTFHR A1298C mutation was detected in the patient who had mastoiditis and meningitis and protein S deficiency and lupus anticoagulant were found in another patient who had mastoiditis. All patients received anticoagulant treatment and all patients recovered without neurological sequelae except one.Conclusions: Cerebral sinovenous thrombosis should be considered in patients who present with headache and focal neurological deficits. Appropriate utilization of imaging studies is necessary for the diagnosis. Detailed ear, nose and throat examination should be performed to detect mastoiditis. It is recommended that genetic risk factors should be investigated, because hereditary thrombophilis factors may have a role in children. Behçet's disease which is relatively common in our country should be considered in differential diagnosis.
Evaluation of cases with cerebral thrombosis in children
Keywords: Hematoloji; Tıbbi Araştırmalar Deneysel; Pediatri